G299(P) Common themes across child safeguarding activity and improving practice. (27th April 2016) - Amirthanayagam, A; Lim, A; Ioannou, Y
Abstract : Aim: Child safeguarding is fundamental to good paediatric practice. This study aimed to analyse the database of all child safeguarding cases presenting to a tertiary hospital, to identify any trends that could contribute towards improving practice and assist in developing staff training programmes. Methods: Every safeguarding presentation is input into a child safeguarding database. All presentations including new safeguarding concerns, social worker notifications and additional support referrals, within a year were analysed retrospectively. The nature of the safeguarding concerns were classified using the details of the background of each presentation into child and adolescent factors (CAF), parental factors (PF), neglect, notification of medical problems, physical, sexual and emotional abuse. Both PF and CAF were sub-divided into substance and alcohol misuse, mental illness and others. CAF also had a subcategory for self-harm, while PF had additional sub-categories for domestic abuse, intellectual disabilities and difficulties coping. Results: The total number of referrals was 924. 63.7% were social worker notifications, 32% new safeguarding concerns and 4.2% for additional support. Conclusion: The data has demonstrated the breadth of safeguarding presentations and activity across a tertiary hospital. A significant proportion of safeguarding presentations involve issues relating to parents and adolescents. A key link between adult and paediatric emergency departments is the paediatric liaison health visitor (PLHV). Data from this study has been used by the PLHV during training of adult emergency staff to highlight the importance of parental factors in child safeguarding presentations. The results have also supported the development of electronic alerts notifying the PLHV of concerns raised in adult presentations. Trust safeguarding training and policy has now been modified to include scenarios and management advice relating to young people with self-harm, substance and alcohol misuse issues. While this study has highlighted that the burden of safeguarding activity lies with parental and adolescent factors, robust staff training and senior supervision remain key to ensuring that the whole range of safeguarding presentations are recognised and the appropriate response to these concerns initiated.